EVALUASI PENERAPAN METODE TIME AND MATERIAL PRICING DALAM MENENTUKAN HARGA JUAL JASA SERVICE DAN SPAREPART PADA CV PRIMA MOTOR DEALER YAMAHA LUWUK - Lalenoh, Marsellino Alexander; Pusung, Rudy J. (Universitas Sam Ratulangi, 2021)
The selling price needs to be determined properly in order to be able to cover all costs incurred issued by the company. One way to determine the selling price is to use the method time and material pricing. This study aims to determine the selling price of services service and spareparts better with method, time and material pricing and to know the selling price of such a method by method used CV Prima Motor Luwuk. This type of research is descriptive quantitative, with quantitative analysis method through calculation of method time and material pricing. Based on the research results, CV Prima Motor Luwuk has not used the method time and material pricing. From the results of calculations using the method time and material pricing, it is found that the selling price of services is cheaper, while the selling price of spareparts is more expensive. With this method, the selling price of service and spareparts will be better because it can increase the company's profit.